Pengaruh Arus Kas Operasi, Financial Leverage Dan Likuiditas Terhadap Return Saham Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) - Nurmeilita, Tasha; Elisabect, Elisabect; Izzati, Nur; Adilatu, Muhamad; Nugroho Budi Wirawan (Awatara Publisher, 2025)
This study aims to examine the effect of operating cash flow, financial leverage, and liquidity on stock return in companies listed on the Jakarta Islamic Index (JII) for the period of 2021–2023. The research is motivated by the fluctuation in stock returns and financial conditions of JII companies, which are influenced by various fundamental factors. This study uses a quantitative approach with multiple linear regression analysis. The data used are secondary data obtained from 10 actively listed companies in the JII. The results show that, partially, operating cash flow has no significant effect on stock return, financial leverage also shows no significant effect, and liquidity likewise does not significantly affect stock return. Simultaneously, the three variables do not have a significant impact on stock return. These findings suggest that stock returns in JII companies during the observed period are influenced by other factors beyond operating cash flow, financial leverage, and liquidity. This research is expected to provide useful insights for investors, companies, and capital market regulators in making strategic decisions in the Islamic stock market.